New Operating System. (Beijing Review, 2025)
The article focuses on Huawei's announcement regarding its HarmonyOS operating system, highlighting that over 23 million devices are currently running HarmonyOS 5 as of October 22. Huawei has begun rolling out HarmonyOS 6 for more than 90 device models, featuring improvements in fluency, intelligence, privacy protection, and cross-device collaboration. Notable enhancements in HarmonyOS 6 include AI-powered anti-fraud capabilities and AI anti-peeping technology for better privacy protection. HarmonyOS is recognized as one of the world's top three mobile operating systems, developed by Huawei.